2021
DOI: 10.1167/tvst.10.12.24
|View full text |Cite
|
Sign up to set email alerts
|

The Ocular Microbiome Is Altered by Sampling Modality and Age

Abstract: Background Studies of the ocular microbiome have used a variety of sampling techniques, but no study has directly compared different sampling methods applied to the same eyes to one another or to a reference standard of corneal epithelial biopsy. We addressed this lack by comparing the microbiome from three conjunctival swabs with those of corneal epithelial biopsy. Methods Twelve eyes (11 patients) were swabbed by calcium alginate swab, cotton-tipped applicator, and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Our evidence showed, in agreement with other studies, that OSM was paucibacterial, but with a predominance of Proteobacteria , Actinobacteria and Firmicutes phyla [ 33 , 34 ]. Figure 1 shows a difference in the percentage of the Bacteroidetes group.…”
Section: Discussionsupporting
confidence: 93%
“…Our evidence showed, in agreement with other studies, that OSM was paucibacterial, but with a predominance of Proteobacteria , Actinobacteria and Firmicutes phyla [ 33 , 34 ]. Figure 1 shows a difference in the percentage of the Bacteroidetes group.…”
Section: Discussionsupporting
confidence: 93%
“…One of the limitations is the long duration of this study, and we did not collect sampling environment-negative controls, although we adopted strict environmental sterilization during each sample collection. Second, previous studies had revealed that the microbiota diversity on the ocular surface of healthy participants changes with age (Suzuki et al, 2020;Katzka et al, 2021). Participants' age ranged from 20 to 60 years in this study, and this age range may have affected the results.…”
Section: Discussionmentioning
confidence: 83%
“…A drop of oxybuprocaine hydrochloride eye drops was used for anesthesia before sampling. ( Ren et al., 2020 ) The superior palpebral conjunctiva, superior bulbar conjunctiva, inferior bulbar conjunctiva, inferior fornical conjunctiva, and inferior palpebral conjunctiva of the examined eye were rubbed lightly in sequence using one sterile cotton swab ( Katzka et al., 2021 ) (from the supply department of Qingdao Eye Hospital of Shandong First Medical University according to T/CSBME013-2019 standard of China) soaked with oxybuprocaine hydrochloride eye drops. ( Ren et al., 2020 ) The meibomian orifices, eyelashes, and cornea were avoided.…”
Section: Methodsmentioning
confidence: 99%